Implementation of Islamic Business Ethics in Micro, Small And Medium Enterprises in Dasri Village - Zuni Maulidia; Wiwit Mustafidah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the implementation of Islamic business ethics in micro, small and medium enterprises (MSMEs) in Dasri Village. The research uses a qualitative method with a descriptive type of research. Data collection techniques with interviews, observations and documentation. The results of the study show that MSME actors in Dasri Village have applied Islamic business ethics principles, including honesty in transactions, not using oaths, and clear pricing. The average business actor shows awareness of the importance of praying before selling and providing generous service to customers. The conclusion of this study confirms that the application of Islamic business ethics among MSMEs in Dasri Village is quite good, creating a more ethical and sustainable business environment.